Synthesis, Crystal Structure, and Fluorescent Property of an Ag(I) Complex With 3-(Benzoimidazol-2-yl)propanoic Acid. Issue 12 (1st December 2016) - Fu, Wei-Wei; Liu, Ying-Ying; Zhang, Yan-Hua; Xu, Liu; Zhang, Jun-Lan; Wei, Hai-Bo
Abstract : A silver complex, Ag(L)(2, 2′-bpy)(H2 O)2 (1 ), has been synthesized with 3-(benzoimidazol-2-yl)propanoic acid (HL) and 2, 2′-bipyridine (2, 2′-bpy) and characterized by IR, elemental analysis, TGA, and single-crystal X-ray diffraction. The complex crystallizes in monoclinic system with space group P2(1)/c, a = 10.6088(4), b = 12.3566(3), c = 15.3319(5) Å, β = 101.668(4)°, V = 1968.31(11) Å 3, Dc = 1.634 g/cm 3, Z = 4, F (000) = 972, final GOF = 1.058, R = 0.0334, and wR = 0.0895 for 3469 observed reflections with I > 2σ(I) . The crystal structure analysis shows that a three dimensional network was formed by hydrogen bonds and π-π interactions. The fluorescence property of1 has been investigated.